2020
DOI: 10.1371/journal.pmed.1003393
|View full text |Cite
|
Sign up to set email alerts
|

The risk of Plasmodium vivax parasitaemia after P. falciparum malaria: An individual patient data meta-analysis from the WorldWide Antimalarial Resistance Network

Abstract: Background There is a high risk of Plasmodium vivax parasitaemia following treatment of falciparum malaria. Our study aimed to quantify this risk and the associated determinants using an individual patient data meta-analysis in order to identify populations in which a policy of universal radical cure, combining artemisinin-based combination therapy (ACT) with a hypnozoitocidal antimalarial drug, would be beneficial. Methods and findings A systematic review of Medline, Embase, Web of Science, and the Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 61 publications
2
31
1
Order By: Relevance
“…This increment of the prevalence of P.vivax causing malaria with the decline of P. falciparum related malaria might also be supported by the fact of reporting Duffy independent invasion and genetic diversity of P.vivax leading to generation of new parasite strains that can translate into parasite's greater adaptability to new challenges for treatments and control measures [47]. Previous meta-analysis found high risk of P.vivax malaria after treatment of P.falciparum malaria [52].…”
Section: Discussionmentioning
confidence: 93%
“…This increment of the prevalence of P.vivax causing malaria with the decline of P. falciparum related malaria might also be supported by the fact of reporting Duffy independent invasion and genetic diversity of P.vivax leading to generation of new parasite strains that can translate into parasite's greater adaptability to new challenges for treatments and control measures [47]. Previous meta-analysis found high risk of P.vivax malaria after treatment of P.falciparum malaria [52].…”
Section: Discussionmentioning
confidence: 93%
“…It was also due to the potential spread of ACT resistance in sub-Saharan Africa because of the progression of chloroquine resistance and sulfadoxine–pyrimethamine resistance from Asia to sub-Saharan Africa in the past, which contributed to millions of childhood deaths [ 40 , 41 ]. Previous studies reported the incidence of P. vivax parasitemia after the treatment of P. falciparum or mixed Plasmodium species in Southeast Asia [ 21 , 28 , 42 ]. Therefore, the efficacy of antimalarial treatment to prevent the recurrence of P. vivax parasitemia is an important consideration for clinical drug trials of malaria control strategies in this region.…”
Section: Discussionmentioning
confidence: 99%
“…The share of P. vivax malaria and anti-malarial drug resistance has increased over the past two decades [ 4 ]. A meta-analysis of patient data from three sites in Bangladesh showed that 12–26% of P. falciparum malaria patients were at risk of P. vivax parasitemia after several weeks following treatment [ 87 ].…”
Section: Epidemiological Data From Countries Of Origin For Importementioning
confidence: 99%